Cataplexy as a side effect of modafinil in a patient without narcolepsy - Eduardo Lopes; Danielle Pereira; Nilce Sanny Costa da Silva Behrens; Hassana de Almeida Fonseca; Paola Oliveira Calvancanti; Taís Figueiredo de Araújo Lima; Marcia Pradella-Hallinan; Juliana Castro; Sergio Tufik; Fernando Morgadinho Santos Coelho (Sleep Science, 2014)
Narcolepsy is a disease in which there is diurnal excessive sleepiness with sleep attacks and a prevalence in the general population of 1/4000 individuals. Classically, it is characterized by cataplexy, sleep paralysis, hypnagogic hallucinations and fragmented sleep. The use of modafinil in the treatment of narcolepsy is the first option of treatment for diurnal excessive sleepiness. Although considered a safe drug for use in patients with narcolepsy, being utilized for more than 20 years, modafinil possesses a series of side effects, some of them still not fully researched or described. Side effects such as headache, nausea, anxiety, insomnia, lumbago, diarrhea, dyspepsia, rhinitis and vertigo are the most frequent. However, the clinical follow-up of patients under treatment with modafinil must be intensive and the side effects ought to be noted and evaluated. The under-response to treatment or the unexpected side effects must always be directed to differential diagnostics. The objective of this article is to describe an unexpected side effect of the use of modafinil in a patient with incorrect diagnosis of narcolepsy.